Respiratory mechanics analysis in neurocritical patients admitted to a general icu ventilated in prvc, pcv and vcv modes - dos Santos Martins, Gabriela (2024)
Objectives: Compare volume controlled (VCV), pressure controlled (PCV) and pressure regulated and volume controlled (PRVC) ventilation modes in relation to ventilatory mechanics in neurocritical patients admitted to an ICU setting. Methods: Sixteen patients were recruited, they had mean age of 56.1±19.7, had 12.6±9.1 days of hospital length of stay, with 81.2% overall survival. Three groups used different ventilatory modalities: PRVC, PCV and VCV. Patients were ventilated for a tidal volume of 6 to 8 ml/Kg, Glasgow, RASS, PAM, FC, f, FiO2, PEEP, pressure, volume or support pressure, Ppico, Cd, Wr, P0.1, pH, PaCO2, PaO2, HCO3 and SaO2 were measured. Results: We did not find differences between the initial and final values and between the groups regarding ventilatory mechanics of the 16 patients on mechanical ventilation admitted to the ICU. We found a correlation between respiratory work and peak pressure (r = 0,87; p = 0,02), expiratory resistance and peak pressure (r = 0,91; p = 0,01), static compliance and elastance (r = -0,81; p = 0,04) and work of breathing and inspiratory resistance (r = 1,0, p = 0,003), in the PRVC mode; correlation between peak pressure and dynamic compliance (r = -0,91, p = 0,03) and work of breathing and elastance (r = -0,90, p = 0,03) in the PCV mode; correlation between elastance and static compliance (r = -0,97, p = 0,004) and PaO2/FiO2 ratio and work of breathing (r = 0,99, p = 0,02) in the VCV mode. Conclusions: There is no difference in ventilatory mechanics parameters when neurocritical patients were mechanically ventilated in PRVC, PCV and VCV modes.